Using Areal Interpolation Techniques and Location Allocation Models to determine the accessibility to Primary Health Care Centers in Al-Rass City - Alkhalifah, Ashwag Mohammed; Alshwesh, Ibrahim Obaid (Journal of Humanities & Social Sciences, 2019)
In this research, the distribution of primary health care centers in Al-Rass city was identified and analyzed of the accessibility to reach it, the research used remote sensing technology represented in Areal Interpolation Techniques by applying a Dasymetric mapping technique to detect the actual spatial distribution of the Al- Rass population to find optimal distribution of the centers based on population numbers and their actual distribution within the neighborhoods, remote sensing is integrated with GIS in data integration, analysis and interpretation represented in this research with Location- allocation models implemented by p-median form to find the optimal centers location that provide coverage to the population within the scope of its services within 800m and 1200m distance the results showed that when applying a 800m distance 58% of the total population becomes out of the geographical coverage of the centers which don’t provide them with easy access, the ratio drops to 34% at a 1200m distance, the location of the optimal centers vary according to the distance traveled to them. Finally the research recommended to take of the result of the result of P-median model for the optimal primary health care centers distribution in Al-Rass city and to select the locations of the future centers based on the outcome of the model.